Studi Pergeseran Signifikansi Elemen Bersejarah Berdasarkan Kognitif Masyarakat Kota - WFF Anwar; Caroline; I Bayusari (Archvisual: Jurnal Arsitektur dan Perencanaan, 2022)
There are areas and historical elements of the city which can still be found physically and some physically no longer exist. In areas where the physical can still be found, the community's cognitive of its existence can still be easily detected. Things are different in historical areas where the physical elements are no longer exist. Palembang has these two situations. Previous study on the significance of city elements conducted in 2019 and 2020 shows there are 22 historical elements of the city that are important. All of them are the exists element buildings that can be found physically. Among of them, there are three elements that were the most significant in terms of memorability, imagibility, and attachment. The three elements are Kuto Besak Fort, Ampera Bridge, and the Great Mosque. This study aims to strengthen the findings by determining important historical elements and areas based on the cognitive of the urban community. This research has two objectives: (1) determine historical elements and areas; and (2) map physical and spatial patterns of elements and/or areas that are considered significant by the community. For this reason, the study mapped elements of the historical area using the mental map results from 30 respondents and then mapped it in the structure of the Palembang city map. The results confirm that these three elements are the most inherent elements in the respondents cognitive. Some of the new elements are listed in the mental map result as new city elements and old elements with new names. This study found that areas and historical elements of the city that physically still exist are more embedded in people's cognitive than those that do not exist and only remain in name (toponym). The conclusion of this study is that efforts are needed to revive the cognitive understanding of the community through reconstruction in digital form.